2013
DOI: 10.1182/blood-2012-08-450502
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the interaction of fibroblast growth factor-2 with the lymphatic endothelial cell marker LYVE-1

Abstract: • FGF2 is able to directly interact with LYVE-1 and glycosylation of LYVE-1 is important for the interaction with FGF2.• LYVE-1 inhibits FGF2-dependent lymphangiogenesis and FGF2 modulates LYVE-1's endogenous expression and reverses the effect of TNF␤.LYVE-1 (lymphatic vessel endothelial hyaluronan receptor-1) is a homolog of the hyaluronan receptor CD44, and one of the most widely used markers of lymphatic endothelial cells in normal and tumor tissues. However, the physiologic role of LYVE-1 in the lymphatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 44 publications
3
58
0
Order By: Relevance
“…Overexpression of VEGF-A 164 leads to the formation of giant lymphatic vessels in the mouse ear [37]. bFGF, on the other hand, can directly interact with the Lyve-1 receptor and, furthermore, upregulate the expression of Lyve-1 in cultured lymphatic ECs and in vivo in a corneal lymphangiogenesis assay [38]. In the PE, lymphangioblasts were not detected [39], consistent with our results.…”
Section: Discussionsupporting
confidence: 79%
“…Overexpression of VEGF-A 164 leads to the formation of giant lymphatic vessels in the mouse ear [37]. bFGF, on the other hand, can directly interact with the Lyve-1 receptor and, furthermore, upregulate the expression of Lyve-1 in cultured lymphatic ECs and in vivo in a corneal lymphangiogenesis assay [38]. In the PE, lymphangioblasts were not detected [39], consistent with our results.…”
Section: Discussionsupporting
confidence: 79%
“…These results indicate that FGF2 acts indirectly to promote lymphangiogenesis. Interestingly, LYVE1, a common lymphatic marker with elusive function, was recently found to bind FGF2 and to promote FGF2-induced signaling activation and lymphangiogenesis (67). Overall, such results could be explained if, for example, FGFR1 and VEGFR3 bind a common signal transducer in LECs.…”
Section: Lymphangiogenic Pathways and Mechanisms Vegfc/d And Vegfr3mentioning
confidence: 79%
“…A recent study indicated that soluble LYVE-1 may interfere with migration and proliferation of LECs by binding directly to fibroblast growth factor-2 (FGF-2) in vitro and in vivo (24). FGF-2 and VEGF-C collaboratively promote tumor growth, angiogenesis, intratumoral lymphangiogenesis, and metastasis (25).…”
Section: Discussionmentioning
confidence: 99%